Effect of a multi-tiered dispatch system on out-of-hospital cardiac arrest patients: preliminary report from the Gyeonggi province, South Korea - Cho, Kyung Hune; Park, Jong-Hak; Moon, Sung Woo; Yun, Seong-Keun; Kim, Jin-young (Clinical and Experimental Emergency Medicine, 2018)
In South Korea, the Gyeonggi Fire Services introduced a multi-tiered dispatch system for out-of-hospital cardiac arrest (OHCA) cases in July 2015. In this study, we investigated whether the multi-tiered dispatch system improved the pre-hospital return of the spontaneous circulation (ROSC) rate. All non-traumatic adult OHCAs treated and transported by the 119 emergency medical system from July 2015 to December 2015 were included in the study. Demographic and pre-hospital Utstein element-data were collected from the emergency medical system OHCA database. The primary outcome was pre-hospital ROSC as measured at the scene. Of the included OHCAs, 1,436 (89.0%) were categorized to the single-tiered dispatch group and 162 (10.1%) to the multi-tiered dispatch group. The rate of administration of advanced airway ventilation (61.1% vs. 48.0%, P=0.002) and intravenous access (18.5% vs. 12.5%, P=0.037) was higher in the multi-tiered group compared to that in the single-tiered group. The use of epinephrine was higher in the multi-tiered group (4.9% vs. 1.5%, P=0.002). The pre-hospital ROSC rates in the multi-tiered group were higher when compared with the single-tiered group, but the difference was not significant (10.5% vs. 7.5%, P=0.218). The adjusted odds ratio for pre-hospital ROSC rates in the multi-tiered group was 1.29 (95% confidence interval, 0.69 to 2.40). The multi-tiered dispatch system was not associated with a significant increase in the pre-hospital ROSC rate during the early phase of its implementation, even though advanced maneuvers were performed more frequently.